2011
DOI: 10.1097/tp.0b013e318223d817
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis and Normothermic Perfusion—Preliminary Experiments in a Porcine Model

Abstract: This study suggests that steatotic livers can be successfully preserved using normothermic preservation for prolonged periods and that normothermic preservation facilitates a reduction in hepatic steatosis. Further studies are now needed including transplantation of steatotic livers after normothermic preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
3
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 27 publications
2
113
3
4
Order By: Relevance
“…Attempts to defat steatotic rat livers during MMP failed to demonstrate histological, hemodynamic, and metabolic improvements (65), unlike previous defatting studies performed using NMP (66,67). Also, postreperfusion liver microarchitecture and bile production have been shown to be significantly improved when MP is performed at normothermic versus midthermic or sub-normothermic temperatures (45).…”
Section: Smpcontrasting
confidence: 38%
“…Attempts to defat steatotic rat livers during MMP failed to demonstrate histological, hemodynamic, and metabolic improvements (65), unlike previous defatting studies performed using NMP (66,67). Also, postreperfusion liver microarchitecture and bile production have been shown to be significantly improved when MP is performed at normothermic versus midthermic or sub-normothermic temperatures (45).…”
Section: Smpcontrasting
confidence: 38%
“…In a preliminary study using steatotic porcine livers, Jamieson et al showed a 50% reduction in the steatosis level after 48 hours of NELP. (34) Moreover, normothermic perfusion of steatotic livers from obese Zucker rats using a "defatting cocktail" led to a 50% reduction in intracellular lipid content after 3 hours of machine perfusion. (25) In our preliminary experiments, we employed 2 steatotic human livers not suitable for clinical transplantation and used a defatting protocol at the beginning of NELP.…”
Section: Discussionmentioning
confidence: 99%
“…Matched control patients were identified as described above; to find two matched controls, preset criteria were extended in some cases, MELD was 12 in NMP versus 14 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) in matched controls (p = 0.55).…”
Section: Donor and Recipient Characteristicsmentioning
confidence: 99%